THE ROLE AND IMPORTANCE OF AVIATION FUEL IN THE HEALTH-SEEKING BEHAVIOR OF CHILD MIGRANTS LIVING ALONG THE UGANDA–KENYA BORDER AT BUSIA - Bateganya, Fred Henry; Nakanjako, Rita (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
This study aimed to understand the health-seeking behaviors of the child migrants, commonly known as Chokola, who live along the Uganda–Kenya border at the town of Busia. The study used qualitative data collection methods: in-depth interviews, life-histories, focus group discussions, and key informant interviews. At the border, Chokola are accorded a marginal status and identity, limiting their health rights. Chokola face many health challenges, some of which arise from risky sexual behaviors and practices. Their health problems include gonorrhea, HIV, malaria, and cholera. The Chokola in our study exhibited specific health-seeking behaviors, with sniffing aviation fuel being the most pronounced. Although this practice was intended to alleviate common ailments and discomfort, it was also reported to have side effects ranging from loss of appetite to early death. Sniffing aviation fuel as a health-seeking behavior is a construction of individuals. Chokola constructions of the efficacy of aviation fuel are inculcated during socialization and are supported by a shared belief in the fuel as a panacea. Scientific views regarding the risks of side effects are irrelevant to them. In terms of access to health services, Chokola are vulnerable and require affirmative action and targeted interventions.